Physical design of a compact injector for synchrotron-based proton therapy - Qiao, Jian; Yan, Nan; Huang, Zike; Zhong, Yang; Wang, Jiazhou; Xie, Xiucui; Pu, Yuehu; Hu, Weigang (Frontiers in Physics, 2023)
A compact room-temperature linear injector has been purposed to accelerate 18.0 mA proton beam to 7.0 MeV for synchrotron-based proton therapy. The total length is about 5 m. It mainly consists of a 3.01 m radio frequency quadrupole (RFQ) and a 0.82 m compact inter-digital H-mode drift tube linac (IH-DTL) structure. Based on a fast-bunching strategy, the RFQ, operated at 325 MHz, accelerates protons to 3.0 MeV. The phase advances have been taken into consideration, and parametric resonance has been carefully avoided by adjusting the vane parameters. After a compact external matching section, the IH-DTL, based on modified KONUS dynamics, accelerates protons up to 7.0 MeV. It is composed of a re-bunching section and an accelerating section. The accelerating gradient reaches 4.88 MV/m. The overall dynamic simulation results show that the whole accelerating gradient has reached up to 1.62 MV/m with transmission efficiency above 95%. The transverse and longitudinal normalized rms emittance at the exit of DTL is 0.23 πmm·mrad and 2.216 πkeV/u·ns, which meet the synchrotron injection requirements. The details of the specific design of this injector are presented in this paper.